PI/NCC-Based Tubular Carbon Membrane: Influence of Aging Times Towards Oxygen Separation Performance - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; A. F., Ismail; K., Kadirgama; Mahendran, Samykano; G., Najafi; Nur Izwanne, Mahyon (Akademi Baru, 2018)
Tubular carbon membrane was prepared from carbonization of P84 co-polyimide (PI) and nanocrystalline cellulose (NCC) which had been carbonized under Argon atmosphere at 800°C with a heating rate of 3°C/min. The resultant TCMs were aged for a specified duration (new, three days, one month, and three months) to study the effects of aging times on the oxygen separation properties (permeance and permselectivity) of TCMs. The investigation finding reveals that the aging times could be a factor that affects the transport properties of the fabricated membrane. The pores of the fabricated TCMs samples tend to shrink over time to reach a stable thermodynamic state. The results also showed that newly fabricated TCMs (no aging) possess the highest gas permeance and perm-selectivities over the aged TCM samples. The highest selectivity was achieved at 9.29±2.5.